THE EFFECT of 4-METHOXYBENZALDEHYDe AND CYCLOHEXANONE MOLE RATIO VARIATION ON THE SYNTHESIS of 2-(4’-METHOXYBENZYLIDENE)CYCLOHEXANONE USING MICROWAVE ASSISTED ORGANIC SYNTHESIS METHODS - Elga Riesta Puteri; Sri Handayani (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2017)
This research aims to determine the effect of mole ratio variation and mole ratio which produce maximum yield. Synthesis of 2-(4’-methoxybenzylidene)cyclohexanone was done through Claissen Schmidt condensation with NaOH as catalyst. Variation of 4-methoxybenzaldehyde:cyclohexanone mole ratio were 1:1, 1:2, 1:4, 1:6, and 1:8. 2-(4’-methoxybenzylidene)cyclohexanone could be synthezied using MAOS methods for 120 seconds. Synthesis product was identified by TLC, TLC scan, spectroscopy IR, and spectroscopy 1H NMR. The result of this research showed that the variation of 4-methoxybenzaldehyde:cyclohexanone mole ratio had an effect on the synthesis of 2-(4’-methoxybenzylidene)cyclohexanone. It was proven by the different of yields which have been produced. Variation of 4-methoxybenzaldehyde:cyclohexanone mole ratio 1:1, 1:2, 1:4, 1:6, and 1:8 produced 2-(4’-methoxybenzylidene)cyclohexanone 0%; 59.272%; 64.122%; 46.782%; and 45.555% in yields respectively. The mole ratio of 4-methoxy-benzaldehyde:cyclohexanone which gives the maximum yield is 1:4.